Preliminary Exploration of the Relationship between Veteran Family Membership, School Climate, and Adverse Outcomes among School-Aged Youth. Issue 5 (June 2022) - Sullivan, Kathrine; Dodge, Jessica; Williamson, Victoria; Alves-Costa, Filipa; Barr, Nicholas; Kintzle, Sara; Fear, Nicola T.; Castro, Carl
Little is known about the functioning of children in veteran-connected families, who may experience a unique constellation of stressors including exposure to parental mental health symptoms and unemployment. Further, research has not previously considered the role of school climate in counteracting these stressors for veteran-connected students. This preliminary study examines the relationship between veteran parent's mental health and employment with adverse outcomes for their school-age children, as well as the potential moderating effect of safe school climate. Participants were 218 veteran parents of children in K-12 schools, who completed the Chicago Veterans Survey, including measures of PTSD and depression, unemployment, a school safety scale drawn from the California School Parent Survey, and an adverse child functioning screening tool. Regression models suggest that depression symptomatology and perceptions of less safe school climate were significantly associated with adverse outcomes among veteran-connected students. Safe school climate buffered against the negative effects of parents' depression symptoms, particularly at lower levels of depression severity. Findings suggest the need for future research to explore the potentially crucial role for schools, including teachers, administrators, and particularly school-based mental health providers, in supporting the healthy functioning of veteran-connected students and their families.